Inheritance and the right to bequeath : legal and philosophical perspectives - Schmidt am Busch, Hans-Christoph; Halliday, Daniel, 1981-; Gutmann, Thomas (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2022)
"In every western democracy today, inheritances have a very profound influence on people's lives. This motivates renewed scholarship on inheritance law by philosophy and the legal sciences. The present volume aims to contribute to some ongoing areas of inquiry while also filling some gaps in research. It is organised in a highly interdisciplinary way. In the sixteen chapters of the book, written by outstanding philosophers and legal scholars, the following questions, among others, are discussed. What is the nature of the right to bequeath? What are the social functions of bequest and inheritance? What arguments concerning justice have philosophers and legal scholars advanced in favour or against practices of bequest and inheritance? How should we think about taxing the wealth transfers that occur in bequest and inheritance? In discussing these questions, the authors break new ground and offer much-needed insight into a number of related domains, such as the philosophy of law, legal theory, general and applied ethics, social and political philosophy, theories of justice and the history of legal, political and economic thought. Engaging the philosophy of law, legal theory, general and applied ethics, social and political philosophy, theories of justice and the history of legal, political and economic thought, this book will be of great interest to scholars in these areas as well as policy makers"--
Introduction / Thomas Gutmann, Daniel Halliday, Hans-Christoph Schmidt am Busch -- What, if anything, is wrong with bequest? / Stefan Gosepath -- The morality of charitable bequests / Miranda Perry Fleischer -- Is the right to bequeath a supernatural power? / Hillel Steiner -- The right to bequeath as a common legal power / Constantin Luft and Thomas Gutmann -- Property rights and the power to transfer / Daniel Halliday -- The double function of inheritance : rethinking conditional bequests / Shelly Keiczer-Levy -- Remembrance, esteem, and the right to bequeath / Hans-Christoph Schmidt am Busch -- Inheritance law and the challenge of securing care in old age / Daphna Hacker -- Natural right or convention? / David James -- Property in the tension between family and civil society / Christopher Yeomans -- Inheritance tax justice and family businesses / Christian Neuhäuser -- Taxing wealth and wealth transfers in the 21st century / Jennifer Bird-Pollan.
Keywords: Inheritance and succession; Legacies; Distribution of decedents' estates; Wills; Inheritance and transfer tax -- Law and legislation; Estate planning; Law (Philosophical concept); LAW / Wills; SOCIAL SCIENCE / Death & Dying; SOCIAL SCIENCE / Sociology / Marriage & Family